The Relationship Between Leucine-Rich- α-2-Glycoprotein-1 Plasma Protein with Cervical Cancer - Ramdhani Yusuf, Andi Nurrissa; Rauf, Syahrul; Mailoa, Johnsen; Sunarno, Isharyah; Savitri, Irma; Leonardy, Rudy B. (Journal of Neonatal Surgery, 2025)
Introduction: Leucine-rich-α-2-glycoprotein-1 (LRG-1) has been identified as a significant role in the pathogenesis of disease development, including cancer, and serves as a prognostic marker for cancer. However, there has been no research on the use of LRG-1 as a marker for cervical cancer (CaCx). This study analyzes the relationship between plasma LRG-1 and the stage, histological type, and degree of differentiation of CaCx. Methods: This cross-sectional study was conducted on patients diagnosed with CaCx who underwent examination at our institution. The results of the anatomical pathology examination, including stage, histological type, and degree of differentiation of CaCx, were recorded. Serum LRG-1 was measured using an ELISA kit. Statistical analysis used the Kruskal Wallis, Mann Whitney, and Fisher Exact tests. Results: A total of 88 women diagnosed with CaCx were collected, consisting of 23 patients in the early stage and 65 patients in the advanced stage. There was a significant relationship between plasma LRG-1 levels and the stage of CaCx (p < 0.05). Advanced CaCx had a higher average plasma LRG-1 level than early stage. Histopathological type and differentiation grade were not significantly related to plasma LRG-1 levels (p > 0.05). Conclusion: Plasma LRG-1 can be a biomarker in predicting the stage of CaCx